2020
DOI: 10.2196/17802
|View full text |Cite
|
Sign up to set email alerts
|

User Retention and Engagement With a Mobile App Intervention to Support Self-Management in Australians With Type 1 or Type 2 Diabetes (My Care Hub): Mixed Methods Study

Abstract: Background Mobile health apps are commonly used to support diabetes self-management (DSM). However, there is limited research assessing whether such apps are able to meet the basic requirements of retaining and engaging users. Objective This study aimed to evaluate participants’ retention and engagement with My Care Hub, a mobile app for DSM. Methods The study employed an explanatory mixed methods design. Pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 50 publications
0
21
0
6
Order By: Relevance
“…The promising result of this pilot MCH app project which shows preliminary efficacy, acceptability (as reported in this study) as well as good level of retention and engagement with the intervention [37] will require further confirmation using long term controlled trials in the future. An adaptive randomized controlled trial design [75] may be best suited due to the rapidly evolving nature of mHealth.…”
Section: Long-term Trialmentioning
confidence: 66%
See 1 more Smart Citation
“…The promising result of this pilot MCH app project which shows preliminary efficacy, acceptability (as reported in this study) as well as good level of retention and engagement with the intervention [37] will require further confirmation using long term controlled trials in the future. An adaptive randomized controlled trial design [75] may be best suited due to the rapidly evolving nature of mHealth.…”
Section: Long-term Trialmentioning
confidence: 66%
“…Details of the study methodology have been fully described in a previous publication [37]. In brief, this pilot study (conducted in August to October 2019) employed a mixed-method sequential explanatory design, where participants accessed the intervention over a three-week period and communicated their perceptions through surveys and interviews.…”
Section: Methodsmentioning
confidence: 99%
“…Participants ignoring digital intervention content sent to encourage SB reduction has been reported elsewhere [37]. Mobile app usage tends to have a natural time course with evidence suggesting that mobile app usage is initially high but follows a sharp decline in as little as three weeks [43]. This highlights the engagement struggles that are inherent in [44].…”
Section: Discussionmentioning
confidence: 94%
“…A decline in use over time is, however, typical in eHealth and mHealth [ 97 ]. In their study of a mHealth tool for diabetes management, Adu and Colleagues [ 98 ] found that use steeply declined when reminders were disabled after 2 of the 3 weeks of the trial period. As also supported by participants during the interviews, it is likely that notifications or reminders from the MyStrengths apps could thus have contributed to maintaining user engagement both in terms of duration and frequency of use.…”
Section: Discussionmentioning
confidence: 99%